The Necessity Of Vengeance Reflected In Alexandre Dumas' The Count Of Monte Cristo (1844): A Psychoanalytic Criticism - Mahfudin, Rizal; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research aims at analyzing necessity of vengeance in the Count of Monte Cristo novel by using Psychoanalytic Criticism. The major problem in this research is to describe how necessity of vengeance is reflected in Alexandre Dumas' the Count of Monte Cristo. The research consists of two objectives: analyzing the novel based on structural elements and analyzing the novel based on psychoanalytic criticism. This study uses qualitative research. The object of the study is the Count of Monte Cristo novel written by Alexandre Dumas. There are two kinds of data source: primary and secondary. The primary data source is the text of the novel Alexandre Dumas's Count of Monte Cristo and the secondary data sources are some books and article related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer applies descriptive analysis. The result of the research bears some conclusions: first, based on psychoanalytic analysis, the main character, Count of Monte Cristo, is a man who has a pleasure seeking personality. Second, vengeance is necessary for Count to restore his selfesteem and to punish their enemies in order to make them aware of their mistakes. Last, Dumas writes the Count of Monte Cristo novel as a mirror of society which describes that there are many individuals exacting vengeance in society and also as an advice to society to prevent vengeance as a means of curing the pain.